Factors of juvenile gang culture in Bangladesh: An investigative study in Dhaka - Hossain, Md Lab; Faruk, Md Omar; Siddiqua, Rukhsana (International Journal of Emerging Trends in Social Sciences, 2024)
The objective of the study was to comprehensively analyze factors (motivational and risk) of juvenile gang culture in contemporary Bangladesh. The study employed qualitative methods, utilizing snowball sampling to collect data through in-depth interviews with juvenile gang members from Pallabi (Mirpur). Additionally, twelve Key Informant Interviews (KIIs) were conducted with experts to address specific challenges and preventive measures related to juvenile gangs in Bangladesh. Secondary data comprised official records from the Dhaka Metropolitan Police (DMP). The analysis involved developing themes based on the consistency between primary and secondary data and theoretical aspects. Findings revealed that juvenile gang members are increasingly involved in serious crimes. Motivational factors for gang involvement have included a quest for instrumental gain, pursuit of excitement, expression of identity, protection, and finding friends. Employing Thornberry’s Interactional theoretical lenses, this study has identified several risk factors across multiple dimensions. On an individual level, low self-esteem, prior delinquency, and negative life experiences increase the likelihood of gang involvement. Moreover, family disintegration, inadequate parental attachment and supervision, and a family history of criminal involvement heighten this risk. Furthermore, peer influence is crucial, as juveniles alienated from family and society often seek support from friends, leading to gang affiliation. Lastly, community context plays a substantial role; juveniles in high-crime areas normalize criminal behavior, and community leader endorsement increases the likelihood of gang involvement. This comprehensive analysis highlights the need for multi-sectoral interventions to address the challenges of juvenile gang culture in Bangladesh.